New model of sports tourism with sustainable tourism development to increase tourist arrivals in Central Aceh Regency, Indonesia - Rangkuti, Yoki Afriandy; Setyawati, Heny; Hartono, Mugiyo; Hidayah, Taufiq (Frontiers in Sports and Active Living, 2024)
Introduction This study explores the development and implementation of a new sports tourism product called “Run H2O Ride” as a strategy for sustainable tourism in Indonesia. Methods The research employs a research and development (R&D) methodology, focusing on identifying potential issues, conducting literature reviews, designing the product, validating the design, and undergoing product development. A combination of discussion group forums (FGD) and expert judgment decisions was used to design the new sport tourism model. Results The effectiveness of the model was assessed through limited product tests, main product tests, and operational product tests involving respondents from the local community and tourists. The results indicate that the “Run H2O Ride” model has been well-received, with positive feedback on its suitability and effectiveness in attracting tourists and enhancing the local economy. Discussion The study concludes by recommending further research to refine the model and emphasizes the importance of local government support and community participation in sustainable tourism development. Theoretical implications highlight the significance of sports tourism events in promoting tourism, while practical implications suggest alternative solutions for increasing tourist visits and improving destination image. Policy recommendations for local governments are proposed to adopt and implement sports tourism events, aligning with long-term development plans for regional tourism growth.